Tinjauan Hukum Islam terhadap Akad Biaya Penanganan dalam Transaksi Cash On Delivery pada Marketplace Shopee - Rachmat Bin Badani Tempo; Irsyad Rafi; Alya Namirah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to describe the concept of handling fee contracts and analyze the review of Islamic law on handling fee contract in Cash On Delivery transactions at the Shopee Marketplace. The main questions of this research are; First, how is the concept of Cash On Delivery transaction contract at Shopee Marketplace. Second, how is the concept of handling fee contract. Third, how is the law of handling fee on Cash On Delivery transaction at Shopee Marketplace according to a review of Islamic law. This research is a qualitative research that using the normative and sociological approach. The research conducted a systematic literature review which summarizing the previous research on the topic. Then, the data collection were analyzed using inductive method. The results of this research shos that; First, Cash On Delivery transaction is a type of transaction where the customer pays for a product at the time of delivery. If customer refuse to pay the Cash On Delivery order twice in last sixty days, the customer will not be able to use Cash On Delivery transaction method on the next sixty days. Second, Handling fee is an amount of charge to customer for every check out. The handling fee is count on the top of their transaction subtotal. Third, the handling fee charged by the Shopee Marketplace on the Cash On Delivery transaction method when viewed from the perspective of Islamic law is appropriate, because it meets the pillars and conditions of buying and selling, namely mumayyiz, the seller is the owner of the goods, the goods sold are not najiz, and the satisfaction between seller and buyer.